MENANGKAL RADIKALISE DIGITAL PADA GENERASI Z - Winda permata sari; Zainuddin Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital paradox phenomenon among Indonesia's Generation Z shows that despite having unlimited access to information, their vulnerability to digital extremism remains high. Low levels of critical literacy and a lack of meaning in their search for identity make Gen Z susceptible to provocative narratives that offer identity and purpose in life. This study confirms that internalizing the values ​​of Tawassuth (Islamic moderation) can serve as an ethical and cognitive foundation for enhancing digital resilience. The principles of Tawazun (balance), I'tidal (justice), Tasamuh (tolerance), and Tabayyun (clarification) are strongly relevant to critical digital literacy competencies in identifying misinformation and extremist propaganda. These values ​​serve as an ethical "operating system" that helps Gen Z respond to digital content in a healthy and responsible manner. Therefore, empowering Gen Z requires a holistic approach through education, family, community, and civil society organizations such as Nahdlatul Ulama (NU) and Muhammadiyah.